2018
DOI: 10.4103/sja.sja_472_17
|View full text |Cite
|
Sign up to set email alerts
|

Wilm's tumor with intracardiac extension causing dynamic tricuspid valve obstruction: An anesthetic challenge

Abstract: Wilms’ tumor (WT) is the most common pediatric renal tumor that often spreads to inferior vena cava and sometimes up to right atrium (RA). We describe successful management of 3-year-old child diagnosed with WT having extension up to RA. He was operated under cardiopulmonary bypass and extubated on postoperative day 2 and discharged. Perioperative anesthesia concerns were shock from dynamic tricuspid valve obstruction, intraoperative massive blood loss, and a higher risk of pulmonary thromboembolism during tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
6
1
Order By: Relevance
“…Our study suggests that young and high-risk WT patients who receive intensive treatment regimens (i.e., for bilateral WT) seem to require unplanned PICU admission more often. This finding has not been described previously and is not consistently reflected in the previously reported cases of WT patients with complications requiring PICU admission [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In the SIOP93-01 and SIOP2001 studies, patients aged 6 months to 2 years were shown to have an excellent survival, with a higher event-free survival when compared to older age groups [ 2 , 3 , 32 ].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Our study suggests that young and high-risk WT patients who receive intensive treatment regimens (i.e., for bilateral WT) seem to require unplanned PICU admission more often. This finding has not been described previously and is not consistently reflected in the previously reported cases of WT patients with complications requiring PICU admission [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In the SIOP93-01 and SIOP2001 studies, patients aged 6 months to 2 years were shown to have an excellent survival, with a higher event-free survival when compared to older age groups [ 2 , 3 , 32 ].…”
Section: Discussioncontrasting
confidence: 71%
“…Case reports confirm that children with WT may require unplanned intensive care treatment due to various tumor- and treatment-related emergencies. These cases revealed not only relatively well-known emergencies associated with WT at presentation, such as malignant hypertension and extensive (intracardial) tumor thrombus, but also postoperative hemorrhage, cardiomyopathy and hepatotoxicity, intracranial bleeding, and seizures [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wilms tumor, also known as nephroblastoma [2], is the most common primary renal [1] tumor in children, accounting for 95% of all renal malignancies in children [3]. It is the fourth most common pediatric cancer overall [4].…”
Section: Discussionmentioning
confidence: 99%
“…In sub-Saharan Africa, WT is reported to be the most common solid tumor among children [3] . The typical clinical presentation of WT is an abdominal mass, with or without constitutional symptoms [4,5] . In low and middle countries (LMICs) like Nigeria, however, patients typically present late, by which time the disease has extended beyond the renal bed [3,4,6] .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with metastasis to the heart may be asymptomatic and identified during routine echocardiography. Others may present with abnormal cardiac findings such as dynamic tricuspid valve obstruction, or cardiogenic shock [5,6,8,9] . Wilms tumour is highly chemo-sensitive and curable, with 5-year overall survival (OS) and event-free survival (EFS) in developed countries approaching 90% with the current multi-modal treatment strategies.…”
Section: Introductionmentioning
confidence: 99%